Temporary gardens - Sini, Raffaella (New York Routledge, 2022)
"The last thirty years have seen a surge in temporary gardens. The flexibility and new challenges investing non-permanent landscapes, has made them a creative and stimulating testing ground for a diversified range of professionals and impromptu designers. Raffaella Sini examines the historical evolution of the genre, exploring theory, narratives and strategies employed in over 80 worldwide temporary garden case studies built throughout France, Germany, Spain and Portugal, Italy, Britain, Belgium, Switzerland, Sweden, New Zealand, Canada, Singapore and the United States. Key topics include: Temporary gardens produced within 1970s avant-garde art and 1980s public art -Temporary gardens as opportunities to work with live-processes, involve people, explore concepts related to social justice and ecology -Temporary gardens to re-invent the vocabulary of garden design -Temporary gardens as practices in today's tactical urbanism The book comprehensively decodifies the full range of ephemeral gardens: 'uprooted', 'mobile', 'itinerant', 'movable', 'postmodern', 'installation', 'exhibited', 'conceptual', 'theme', 'pop-up', 'guerilla', 'grassroots', 'meanwhile' 'interim', 'provisional', 'activist', 'community' and 'parklets'. Beyond temporary gardens' physical duration, time-focused design affects the whole process of conceptualizing, building, experiencing, using and managing gardens; using short-term formats, anyone can invent, trial and experiment in a condensed experience of landscape. The temporary garden emerges as a critical cultural ground for the discourse in landscape architecture, art, ephemeral urbanism, urban, landscape and garden design. Inspirational reading for designers and students alike".
Keywords: Temporary gardens; Gardens -- Styles